COOPERATION AMONG EDUCATIONAL INSTITUTIONS NECESSARY TO BUILD A FUTURE OF EXCELLENCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, October 2015 – The spirit of cooperation needs to be established among educational institutions throughout the world to ensure that its progress and development would be in line with the agenda of the respective institutions, in raising the standards of education to more respectable levels.